Legal Consequences of Underage Marriage Practices Reviewed Based on Law Number 23 of 2002 on Child Protection as Amended by Law Number 35 of 2014 (A Case Study in Lempuyang Village, Tanara District) - Aulia Zahra; Dika Ratu marfu’atun; Muhamad Yusar (CV. Era Digital Nusantara, 2025)
This study aims to analyze the causes and legal consequences of underage marriage practices and to examine their application based on Law Number 23 of 2002 on Child Protection, as amended by Law Number 35 of 2014. The research uses a normative juridical method with a statutory and case approach, supported by empirical data collected in Lempuyang Village, Tanara District, Serang Regency. The findings indicate that underage marriage still occurs due to low legal awareness, economic pressure, and strong cultural influences. Legally, such practice contradicts the principles of child protection as it neglects the child’s right to proper growth and development. The lenient granting of marriage dispensation further weakens the enforcement of the law. Based on the Theory of Child Protection and Utilitarian Theory, early marriage provides no legal benefit but instead creates social harm, such as school dropout, poverty, and domestic violence. Therefore, stricter law enforcement and continuous legal education are required to prevent these practices and ensure the protection of children’s rights comprehensively